Implementasi Metode Sokratik Melalui Lesson Study Untuk Meningkatkan Keterampilan Berpikir Kritis Mahasiswa - Ketut Susiani; Kadek Suranata (Universitas Mathla'ul Anwar Banten, 2017)
This article reports the experience of implementing the action research to apply the Socratic dialogue method through lesson study in the lecture of Educational Profession to improve critical thinking skills of the university students. The subject of this action research is 36 students (22 women and 14 men) in grade VI class B, Department Guidance and Counseling (BK), Faculty of Education, Universitas Pendidikan Ganesha (Undiksha) on academic years 2016/2017. This action research conducted in cycles (reported in three cycles) which is integrated into the activities of lesson study. In every cycle consisted of a plan, action, observation/evaluation and reflection phase. Critical thinking skills are assessed through observation activities in group discussion activities and classes, as well as through student response in solving essay test (on cases analysis), which assessed by a rubric assessment of students critical thinking skills at each end of the course. The results showed that the mean of the critical thinking skills of students at the end of the first cycle is 50 (low), then at the end of the second cycle increased to 65 (average) and at the end of the third cycle increased again to 89 (high). Research also shows that the lesson learned were founded through collaborating and careful observation of the course observer with researchers in identifying strengths and constraints and to produce efforts to improve the implementation of the course to improve the quality of learning.